2020
DOI: 10.1002/anie.201913704
|View full text |Cite
|
Sign up to set email alerts
|

Tweaking Nickel with Minimal Silver in a Heterogeneous Alloy of Decahedral Geometry to Deliver Platinum‐like Hydrogen Evolution Activity

Abstract: Five‐fold intertwined AgxNi1−x (x=0.01–0.25) heterogeneous alloy nanocrystal (NC) catalysts, prepared through unique reagent combinations, are presented. With only ca. 5 at % Ag (AgNi‐5), Pt‐like activity has been achieved at pH 14. To reach a current density of 10 mA cm−2 the extremely stable AgNi‐5 requires an overpotential of 24.0±1.2 mV as compared to 20.1±0.8 mV for 20 % Pt/C, both with equal catalyst loading of 1.32 mg cm−2. The turnover frequency (TOF) is as high as 2.1 H2 s−1 at 50 mV (vs. RHE). Site‐s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 53 publications
0
54
0
Order By: Relevance
“…3e and f) and expectedly it is better or comparable to that of the best known catalysts reported to date (Tables S4 and S5 †). 5,[10][11][12][14][15][16][17][18][19][20][21][22][23][24][25][26][27][46][47][48] When coupled to NiFe-LDH, overall water splitting is obtained at 1.508 V by the NiFe-LDH (+) || Cu-m/Cu-W/NiCo-LDH (À) electrolyzer to achieve a current density of 10 mA cm À2 compared to IrO 2 (+) || 40 wt% Pt/C (À) which needs 1.55 V along with exceptional stability for almost 70 h at 333 mA cm À2 , making it suitable for practical applications (Fig. S20 †).…”
Section: Resultsmentioning
confidence: 99%
“…3e and f) and expectedly it is better or comparable to that of the best known catalysts reported to date (Tables S4 and S5 †). 5,[10][11][12][14][15][16][17][18][19][20][21][22][23][24][25][26][27][46][47][48] When coupled to NiFe-LDH, overall water splitting is obtained at 1.508 V by the NiFe-LDH (+) || Cu-m/Cu-W/NiCo-LDH (À) electrolyzer to achieve a current density of 10 mA cm À2 compared to IrO 2 (+) || 40 wt% Pt/C (À) which needs 1.55 V along with exceptional stability for almost 70 h at 333 mA cm À2 , making it suitable for practical applications (Fig. S20 †).…”
Section: Resultsmentioning
confidence: 99%
“…[1] At remendous amount of effort has been devoted to developing cleanersources of H 2 ,s uch as water electrolysis. [2] The process, however,i nvolves two half-reactions, the oxygen and hydrogen evolution reactions (OER and HER, respectively), and hence, there is a growingn eed for next-generation electrocatalysts to minimize any overpotential over the theoretical potential of 1.23 V. [2][3][4][5][6] To move away from expensive benchmark electrocatalysts, such as IrO 2 /RuO 2 /PtÀC-based catalysts, for the OER and HER, efforts are focusedo nd eveloping cheaper earth-abundant catalysts, mainly based on first-row transition metals,n amely,C o, Ni, Fe, and Mn, [7][8][9][10] including their oxides, phosphides,c halcogenides, and nitrides. [11][12][13] Major efforts are directed to inducingasuperior electrochemically active surface area (ECSA), high turnover frequency (TOF), and good pH universality to lower the overpotentials and catalyst mass loading.…”
Section: Introductionmentioning
confidence: 99%
“…Twin defects are widely used in electrocatalysis due to their unique structure characters, and it has also been demonstrated that twin defects play an important role in modulating the HER activity of metal catalysts. [58][59][60] For example, Liu et al found that the twinned Pd 2 CoAg nano-crystals exhibited excellent HER performance in acidic media, in which the enhancement could attributed to the increased active sites caused by surface vacancies and twin boundaries. [58] In addition, Mu and co-workers obtained the five-twinned PtPdRuTe nanocrystal through solution-phase synthesis (Figure 9a-c), and found its higher electrocatalytic activities towards HER compared with the Pt/C in both alkaline and acidic media (Figure 9d, e).…”
Section: Hydrogen Evolution Reaction (Her)mentioning
confidence: 99%